(untitled) (Research, Society and Development, 2021)
The objective of the research is to identify and promote the autonomy of women in situations of violence in their daily lives. Qualitative research articulated with Paulo Freire’s methodological framework, with the production of information through Culture Circles, which are formed by the following steps: thematic research; encoding and decoding; and critical unveiling. Six two-hour Culture Circles were held, with an average of nine participants in each meeting. The investigation revealed eight generating themes and two of them will be discussed in this study: the need for listening and dialogue on aspects of moral and domestic violence and the relationship with health promotion, with a focus on autonomy. The statements show how much the dependency relationships shape a structure of power of the man over the woman, and how much the deconstruction of this paradigm transforms the lives of the victims of violence. Still, public health was highlighted as a space for dialogue that promotes the process of building autonomy, including through moments of sharing and critical reflection, such as Culture Circles. It was possible to identify that the link between the actors involved was built during the study, which contributed to the production of information and to the positive impact generated in the studied context. As possibilities, the occupation of spaces by health professionals stands out to contribute to gender issues, building strategies aimed at solving the problems faced in this area, through the promotion of the health of women victims of violence.